A taxonomic revision and a review of the biology of the North American seed-harvester ant genus Veromessor (Hymenoptera: Formicidae: Myrmicinae) - Johnson, Robert A.; Borowiec, Marek L.; Snelling, Roy R.; Cole, Arthur C. (Zootaxa, 2022)
This paper provides a taxonomic revision and a review of the biology for the 10 species of North American seed-harvester ants in the genus Veromessor. Two new synonomies are proposed: V. julianus subsp. clarior W.M. Wheeler and Creighton 1934 new synonym and V. julianus subsp. manni W.M. Wheeler and Creighton 1934 new synonym are synonomized under V. julianus (Pergande, 1894). One new species is described: V. pseudolariversi new species (worker, queen, male), as a result of splitting V. lariversi Smith into two species based on morphological and genetic differences. We also diagnose previously undescribed queens and males for the following species: V. andrei (male), V. chamberlini (queen, male), V. chicoensis (queen, male), V. julianus (queen, male), and V. stoddardi (queen, male). Information on biology of each species is summarized, along with distribution maps and keys to workers, queens, and males. We then discuss the biology for species of Veromessor, focusing on several morphological and ecological traits that display strong variation across the relatively low number of species (10) in the genus. Morphological traits include degree of psammophore development, propodeal spine length, eye size and structure, and worker polymorphism and worker body size, while ecological traits include colony size and foraging method, seasonality of mating flights, mating frequency, and queen size and colony founding strategy.